2020
DOI: 10.1007/s11033-020-05368-9
|View full text |Cite
|
Sign up to set email alerts
|

Decrypting the crosstalk of noncoding RNAs in the progression of IPF

Abstract: Idiopathic pulmonary fibrosis (IPF) is an agnogenic, rare, and lethal disease, with high mortality and poor prognosis and a median survival time as short as 3 to 5 years after diagnosis. No effective therapeutic drugs are still not available not only in clinical practice, but also in preclinical phases. To better and deeper understand pulmonary fibrosis will provide more effective strategies for therapy. Mounting evidence suggests that noncoding RNAs (ncRNAs) and their interactions may contribute to lung fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…We also checked the data for expression of characteristic miRNAs associated with specific pathological condition. Major miRNAs described in idiopathic pulmonary fibrosis with putative functions in aberrant inflammatory responses and in regulation of extra cellular matrix synthesis, collagen expression, matrix metalloproteases (MMP) expression and epithelial-mesenchymal transition [ 25 , 27 , 36 , 37 ] such as let-7d, miR-145, miR-199, miR-200b/c, miR-21, miR-26a, miR-29a/c and miR-92a (and several others, see Additional file 4 : Table S3) could be detected in human PCLS. miRNAs such as miR-125a/b, miR-145/146a, miR-149, miR-15b and miR-199a (Additional file 4 : Table S3) are described as mediators of the TGFß signaling cascade and of genes with impact on the development and progression of COPD, inflammatory response, and airway epithelial repair after injury.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…We also checked the data for expression of characteristic miRNAs associated with specific pathological condition. Major miRNAs described in idiopathic pulmonary fibrosis with putative functions in aberrant inflammatory responses and in regulation of extra cellular matrix synthesis, collagen expression, matrix metalloproteases (MMP) expression and epithelial-mesenchymal transition [ 25 , 27 , 36 , 37 ] such as let-7d, miR-145, miR-199, miR-200b/c, miR-21, miR-26a, miR-29a/c and miR-92a (and several others, see Additional file 4 : Table S3) could be detected in human PCLS. miRNAs such as miR-125a/b, miR-145/146a, miR-149, miR-15b and miR-199a (Additional file 4 : Table S3) are described as mediators of the TGFß signaling cascade and of genes with impact on the development and progression of COPD, inflammatory response, and airway epithelial repair after injury.…”
Section: Main Textmentioning
confidence: 99%
“…Some RNA therapeutics have been approved or in phase III trials [ 21 ]. Accumulating number of investigations show a pivotal role of miRNAs in the pathogenesis of respiratory diseases such as fibrosis, asthma or chronic obstructive pulmonary disease (COPD) [ 22 27 ]. Given these central role of miRNAs in lung diseases, they are candidates for prognostic or therapeutic biomarkers and novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We also checked the data for expression of characteristic miRNAs associated with specific pathological condition. Major miRNAs described in idiopathic pulmonary fibrosis with putative functions in aberrant inflammatory responses and in regulation of extra cellular matrix synthesis, collagen expression, matrix metalloproteases (MMP) expression and epithelial-mesenchymal transition [25,27,36,37] such as let-7d, miR-145, miR-199, miR-200b/c, miR-21, miR-26a, miR-29a/c and miR-92a (and several others, see Table S3) could be detected in human PCLS. miRNAs such as miR-125a/b, miR-145/146a, miR-149, miR-15b and miR-199a (Table S3) are described as mediators of the TGFß signaling cascade and of genes with impact on the development and progression of COPD, inflammatory response, and airway epithelial repair after injury.…”
Section: Genome-wide Mirna Profiling In Human Pcls and Detection Of Cmentioning
confidence: 99%
“…Some RNA therapeutics have been approved or in phase III trials [21]. Accumulating number of investigations show a pivotal role of miRNAs in the pathogenesis of respiratory diseases such as fibrosis, asthma or chronic obstructive pulmonary disease (COPD) [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA sirt1 antisense was reported to inhibit TGF-β1-mediated epithelial-mesenchymal transition in vitro and alleviate the progression of IPF in vivo 16 . Crosstalk among non-coding RNAs plays a crucial regulatory role in the progression of IPF 17 . Savary et al demonstrated that lncRNA DNM3OS regulates myofibroblast activation by giving rise to profibrotic mature miRNAs, such as miR-199a-5p/3p and miR-214-3p 18 .…”
Section: Introductionmentioning
confidence: 99%